The Attitude of Recidivists Towards the Education in PCI - Knežić, Branislava; Stojanović, Marija (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
The increasing number of recidivists in prisons gives evidence that prisoners cannot be "improved" by deprivation of freedom or repression. There are a number of reasons for inefficiency of institutional resocialization, and it is still an under-explored area of law, criminology, penology, sociology and andragogy. Therefore, the main issue is whether prisoners can be prepared for successful reintegration into society after prison release in an isolated environment such as prison. Education can play an important role in the realisation of this objective. The subject of this text is one aspect of education in prison, i.e., research on prisoners’ attitudes towards education in general and towards educational programs in prison. Also, we were interested in whether prisoners are motivated to participate in the offered educational programs. The empirical research was conducted on a convenience sample of recidivists at the Penal Correctional Institution (PCI) in Sremska Mitrovica. The results show that our sample of recidivists has a more positive attitude towards education in general compared to the offered educational programs in PCI.